Theory of Learning Behavioral, Cognitive and Constructivist - Mohamad Mishbahuddin (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
Abstract: This research aims at four goals to know the oldest theory of learning behavioral, cognitive and constructivist, as well as to benefit from the three theories in teaching the second language of a university student in Indonesia, either the entrance to the research used by the researcher is the qualitative entrance, which is the research that aims to discover the manifestations, and the design of the research is the descriptive design, a research that aims to describe or visualize the manifestations of the occurrence, whether natural or industrial, or the results of this research is knowledge presented by behavioral and cognitive learning theory and constructivism as well as benefiting from the three theories in teaching the second language of a university student in Indonesia. Keyword: behavioral theory, cognitive theory, constructivist theory, benefit in second language education